2013
DOI: 10.1590/s0103-21002013000400002
|View full text |Cite
|
Sign up to set email alerts
|

A biossegurança durante os cuidados de enfermagem aos pacientes com tuberculose pulmonar

Abstract: Objective: To evaluate preventive measures recommended during patient care for respiratory symptoms, with pulmonary tuberculosis. Methods: Exploratory-descriptive study, retrospective, developed from information collected in medical records of patients with respiratory symptoms, diagnosed with pulmonary tuberculosis. Results: The number of tuberculosis cases in the city diagnosed during hospitalization during the study period was 65,29 (44.6%). As for the biosecurity measures during the hospitalization of 29 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
1
0
1
Order By: Relevance
“…Worldwide, patients harbouring Mycobacterium tuberculosis are being cared for in PHC; many of them while at the bacillary phase, mainly in countries with high prevalence [8, 31]. Therefore, it is essential that biosafety measures, such as the use of respiratory protection and cough etiquette, alongside environment control measures, as well as standards for triage and sputum collection from outpatients, are widely adopted in PHC [25, 31, 32]. The data obtained in our study indicated that professionals are unsure about these recommendations, probably due to insufficient in-service standards and training.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, patients harbouring Mycobacterium tuberculosis are being cared for in PHC; many of them while at the bacillary phase, mainly in countries with high prevalence [8, 31]. Therefore, it is essential that biosafety measures, such as the use of respiratory protection and cough etiquette, alongside environment control measures, as well as standards for triage and sputum collection from outpatients, are widely adopted in PHC [25, 31, 32]. The data obtained in our study indicated that professionals are unsure about these recommendations, probably due to insufficient in-service standards and training.…”
Section: Discussionmentioning
confidence: 99%
“…Nas percepções sobre precauções por transmissão, novamente a inconsistência de entendimento se faz presente, pois 47,9% entendem de maneira correta que as precauções baseadas na transmissão são designadas apenas para o cuidado de pacientes conhecidos ou suspeitos de estarem infectados ou colonizados por microrganismos importantes epidemiologicamente e que podem ser transmitidas através de aerossóis, gotículas ou por contato 20. Assim, no que concerne aos tipos de precauções orientadas para a tuberculose pulmonar, verificou-se que 73,9% entende corretamente que o tipo característico é a precaução por aerossóis 21. Entretanto, mais de 25% destes entendem ser a precaução por gotículas, retomando a questão de preocupação com o conhecimento dos profissionais assistenciais.Em outra pesquisa é afirmada que esta infecção se deve a interações ambientais 22.…”
unclassified